A COMPREHENSIVE STUDY ON STUDENTS' ESSAY WRITING SKILLS - I Nyoman Suparsa; Ida Bagus Nyoman Mantra; Ni Luh Sukanadi; I Nyoman Adi Susrawan; I Nyoman Suwandi (Bajang Institute, 2023)
The objective of this study was to investigate the essay-writing skills of students in Indonesian education institutions. A descriptive study approach was used to collect data from a group of students. Students were given three topics to choose from and were instructed to write academic essays within a certain time range. The student writings were gathered and scored using a scoring rubric that assessed several components of the essays. The data obtained were statistically analysed using descriptive analysis to describe the students’ essay writing skills. According to the findings of this study, the majority of students performed modestly on the writing test, with some performing better than others. The research found that the students struggled with organization and consistency, while their grammar and word usage still required to be improved. The study highlights the importance of enhancing students' writing skills to a higher level